Flood risk and property value changes: understanding the impact of climate event exposure in the context of population change - Sandoval Olascoga, Sebastian; Shu, Evelyn; Porter, Jeremy (Frontiers in Environmental Economics, 2025)
IntroductionExposure to flood risk has been linked to property value decreases, negative health/well-being, and both short and long-term population displacement. That being said, our understanding of these consequences is generally limited by geographic scope, due to an overreliance on aggregated case studies of flood exposure, and research design, due to the lack of access to repeated property-level transaction data.MethodsUsing a nationwide high-resolution historic flood exposure event database and longitudinal residential property-level transaction information, this research identifies relationships between neighborhood exposure to flooding and property valuation. Furthermore, this analysis introduces a market component by accounting for the context of growth, and decline, in populations in the area to account for the potentially confounding effect of housing demand.ResultsThe results of the longitudinal, within-property, analysis indicate the average treatment effect of flood exposure on property values is both negative and persistently impactful over time. When paired with future population and flood exposure forecasts, this research further identifies the potential impact of increasing flood exposure on increases in property devaluation 30 years into the future.DiscussionFinally, the elasticity of these negative effects is modeled against property-derived tax revenues and indicates that in some areas of the country, decreasing property values due to flood exposure have had an important impact on community finances and the ability to fund projects related to risk adaptation.